Mecanismos de transferência de tecnologia em uma cadeia de suprimentos verde - Silva Neto, Eugênio Mauricio da (2014)
The increase of the productivity levels combined with higher levels of consumption achieved by the global economies have led companies to turn their efforts to the adoption of green management practices that might offer a differential and, at the same time, meet the demands of the market through a sustainable, technological and innovative production chain. Thus, this research aims to identify mechanisms of technology transfer in a green supply chain of paper. In order to analyze the existence of technology transfer mechanisms, green practices in inbound and outbound logistics, as well as production. This study was classified as an applied, qualitative and exploratory research, with technical procedures via case study. Three industries belonging to a green supply chain of paper were analyzed, selected by accessibility. For data collection, a semi-structured questionnaire with open questions, divided into five constructs, was applied to the managers of these companies, which are able to provide answers to the objectives of this study. The main results of this research reveal the existence of technology transfer mechanisms in the studied green supply chain, directly influencing the production processes of the surveyed companies, from suppliers, processing and distribution of products, with green practices and proposing a framework of mechanisms for technology transfer and knowledge transfering.